Exploring Spinoza A Conversation with Susan James. - Burton, Howard (Ideas Roadshow Conversations Ser., 2021)
This book is based on an in-depth filmed conversation between Howard Burton and Susan James, Professor of Philosophy at Birbeck, University of London. Susan James is an internationally-renowned Spinoza scholar and author of Spinoza on Philosophy, Religion and Politics and Spinoza on Learning to Live Together which are discussed in detail during this wide-ranging conversation. After an inspiring story of how she became interested in philosophy, Susan James provides detailed insights into Spinoza's ideas and their current relevance; the political environment and the theological struggle about wh.